Regional Economic Integration in East Asia: Progress and Pathways - Erlinda M. Medalla; Jenny D. Balboa (Philippine Institute for Development Studies (PIDS), 2011)
The East Asian region is a major global economic player, given its economic size and potential. As such, Regional Economic Integration in East Asia could be considered as an important building bloc toward integration of the Asia-Pacific region. East Asia has made significant progress in creating institutions for closer cooperation and integration. The next step would be how to strengthen support to these mechanisms such that they would effectively deliver the regional goals, as well as help the region overcome pressing issues. This short paper will discuss the state of economic integration in East Asia. It will also discuss the challenges in economic cooperation and integration in the region, as well as some policy strategies to overcome the challenge.
Keywords: 330; regional economic integration; East Asia; free trade agreements (FTAs); forum for cooperation; Regionale Wirtschaftsintegration; Freihandelszone; Handelsabkommen; Ostasien